Evaluation du risque de déstabilisation des infrastructures de haute montagne engendré par le réchauffement climatique dans les Alpes françaises - Pierre-Allain Duvillard; Ludovic Ravanel; Philip Deline (Revue de Géographie Alpine)
Due to ongoing global warming, high alpine environments are affected by significant changes, such as glacial retreat and permafrost warming, which can trigger mass movements in rock slopes or superficial deposits. These processes generate a risk of direct destabilisation for high mountain infrastructures (huts, cable cars, etc.). To help prevent such risks, an inventory of all the high mountain infrastructures in the French Alps was carried out using a Geographic Information System. This combined several data layers, including the Alpine Permafrost Index Map and glacier inventories since the end of the Little Ice Age. 1,769 infrastructures were identified in areas probably characterised by permafrost and/or possibly affected by glacier shrinkage. An index of destabilisation risk was constructed to identify and rank infrastructures at risk. This theoretical risk index includes a characterisation of hazards and a diagnosis of vulnerability. 10 % of the infrastructures were characterised by a high risk of destabilisation.